Theoretical calculation model of time-space effect in subway station construction by PBA - Liu Bo; Fu Chunqing; Li Dongyang; Yang Hang (矿业科学学报, 2021)
Aiming at the problems of structural dimension deviation, initial cracks and apparent defects in beam-column and other structures that occurred during the construction by Pile-Beam-Arch(PBA)approach, Based on the stochastic medium theory, a theoretical analysis model of the space-time effect of group tunnels excavation is established. The causes for the deviation of the building arches caused by the asymmetric construction are analyzed. Taking asymmetric excavation of 8 pilot tunnels in a typical PBA station as an example, the mechanism of uneven changes in stratum space caused by multi-step construction of pilot tunnels in large-span cross-section tunnels is researched. The essential cause of the deviation of the building arches is analyzed, and the deformation law of the surface settlement trough spatial shape swinging left and right with the excavation of the guide tunnel is reconstruced. According to the above research, it is pointed out that the arching being closed and looped, the rapid synchronization operation, the side hole divided into span building arches and construction optimization to achieve symmetric synchronization are the main countermeasures to eliminate or reduce the deviation of building arches.